Young Indigenous Australian children’s English language development and school readiness. - Pope, Adam (My University, 2016)
Indigenous Australian children continue to perform below non-Indigenous children on assessments of English language proficiency and school readiness. This study examined whether in-home language resources, language-specific enrichment activities, and informal and formal general enrichment practices found in Western contexts predict young Indigenous Australian children’s expressive oral language development and more-general school readiness. Participants were drawn from archival data from the Longitudinal Study of Australian Children (LSIC). The sample was obtained from 11 sites across Australia to include urban, rural and remote areas. Data about enrichment practices and resources were sought from parent interviews and developmental assessments of Indigenous Australian children between the ages of 4 and 5 (n = 277). The measure of in-home resources was the number of children’s books in the home. This thesis innovated by adapting more culturally relevant traditional language-specific and more general enrichment activities. The measure of formal general enrichment was preschool attendance. The number of children’s books in the home accounted for a large proportion of variance on scores of expressive oral vocabulary and more general school readiness. Children’s books were found to mediate the relationship between maternal schooling and developmental outcomes. We found no evidence that adapted measures of language-specific or more general enrichment activities predicted Indigenous Australian children’s expressive oral vocabulary or school readiness. Our results provide the basis for further examination whether exposure to children’s books in early childhood predict language proficiency and more general school readiness for Indigenous Australian children.
Keywords: Child Development -- Speech and Language; Culture -- Indigenous; Childhood and child development; Culture; Child Development; Speech and Language; Indigenous; Childhood and child development